(untitled) (Pubmet, 2022)
The Peer Review Information Service for Monographs (PRISM) is offered to publishers who have registered with the Directory of Open Access Books (DOAB) and is provided by the DOAB Foundation on behalf of the OPERAS community. PRISM is currently operating in the beta stage and will move into production in the second half of 2022. It provides information from open access (OA) book publishers about their peer review procedure. The service enables publishers to provide information at both the publisher level and the individual publication level. The goal of the service is to build trust in OA book publishing by improving transparency around quality assurance of OA book publishers and their publications. The service has been tested in partnership with a small and diverse group of commercial and noncommercial, small, medium, and large OA book publishers. Thanks to their involvement, the service has further been improved and made ready to accommodate many more publishers from 2022 onwards. This presentation will describe the background and context for PRISM, its objectives, implementation (including its Scientific Committee), and potential future trajectories. Moreover, the presentation will highlight the relevance of the service for stakeholders other than OA publishers, such as research libraries, readers, and authors. More information about the service is available at https://doabooks.org/en/publishers/prism